“It is not easy to be a parent” – presentation of the main assumptions of the programme intended for the parents benefitting from the help of the Miejski Ośrodek Pomocy Społecznej(the City Social Services Centre) in Wałbrzych - Wójtowicz, Monika (Karkonoska Państwowa Szkoła Wyższa, 2012)
The parenting skills workshop named “It is not easy to be a parent” is an answer to the needs of parents, pedagogues, social workers, and guardians. The article is based on the author’s professional experience. Establishing effective communication with the parents who often feel lost and helpless, and presenting them with ways to bring up their children competently – how to listen to them, how to talk to them, how to set standards, how to support and help them in overcoming difficulties – are the basis of the presented workshops. The author presentsthe main assumptions of the programme as well as the expected results. Other importantfactors supporting the process of parents’ education, i.e. the diagnosis and identification of pedagogic problems, cooperation between institutions, motivational influence, and places and resources are also discussed.
Keywords: family; parenting skills; pedagogic problems; parents education